Rheology of cocoa butter. (September 2021) - Mishra, Kim; Kohler, Lucas; Kummer, Nico; Zimmermann, Simon; Ehrengruber, Silas; Kämpf, Fabian; Dufour, Damien; Nyström, Gustav; Fischer, Peter; Windhab, Erich J.
Abstract: The rheology of β V / V I cocoa butter crystal melt suspensions (CB CMS) was investigated directly after crystallization using in-line capillary rheometry (UVP-PD) as well as after tempering at zero deformation using off-line capillary rheometry (CR) and rotational rheometry (RR). CB CMS thixotropy was quantified by RR revealing that structure build up processes at zero deformation were not at equilibrium after 18 h, whereas structure decay occurred mainly in the first 10 s of measurement at γ ˙  = 60 s −1 . CR and UVP-PD were identified as preferable methods to probe thixotropic materials due to the short measurement time t M and uniform sample deformation history for every γ ˙ -step. The scaling of the relative viscosity η r e l and the (apparent) yield stress τ 0 / τ 0 a p p as function of deformation history revealed two different regimes. Directly after the crystallization, the CB CMS behaved like a suspension of anisotropic crystals with a fractal dimension D ≈ 1.57, an intrinsic viscosity [ η ] of 20 and a maximal packing fraction Φ m a x of 0.17 leading to a scaling of η r e l = ( 1 − ( Φ S F C / Φ m a x ) ) − 3.4 . After tempering at zero deformation, crystal aggregation increased the fractal dimension to D = 2.6 and the scaling of the relative viscosity η r e l reduced to ~ Φ S F C 2, analogously to a jammed system of elastic particles. Graphical abstract: Image 1 Highlights: In-line and off-line rheology of CB CMS. Quantification of thixotropic time scales relevant in CB CMS. Mastercurves for the relative viscosity η r e l and the Herschel-Bulkley parameters τ 0 / τ 0 a p p, n, a n d K . . Fractal dimension and intrinsic viscosity of CB CMS. Single crystal AFM image of CB CMS.